Lumbar Lordosis Distribution in Asymptomatic Adult Volunteers: A Systematic Review. Issue 2 (May 2023) - Ge, Tenghui; Xie, Linzhen; Li, Jianing; Ao, Jintao; Wu, Jingye; Sun, Yuqing
Background: Restoring lumbar lordosis is important for adult spinal deformity surgery. Several reports have suggested that lumbar lordosis distribution has a significant impact on the outcome of surgery, including lumbar distribution index (LDI), proximal lumbar lordosis (PLL), and distal lumbar lordosis (DLL). The features of lumbar lordosis distribution are inconclusive in asymptomatic adults. Questions/Purposes: We sought to evaluate the variation of lumbar lordosis distribution (LDI, PLL, and DLL) and to identify associated factors in asymptomatic adult volunteers. Methods: We performed a systematic review of the Embase and Medline databases to identify studies in asymptomatic adult volunteers to evaluate lumbar lordosis distribution including LDI, PLL, and DLL. Results: Twelve articles met eligibility criteria and were included in our review. The respective pooled estimates of mean and variance, respectively, were 65.10% (95% confidence interval [CI]: 62.61–67.58) and 13.70% in LDI, 16.51° (95% CI: 5.54–27.49) and 11.46° in PLL, and 35.47° (95% CI: 32.79–38.18) and 9.10° in DLL. Lumbar lordosis distribution was associated with race, age, sex, body mass index, pelvic incidence, and Roussouly classification. Conclusions: This systematic review found that despite a wide variation in LDI and PLL, DLL is maintained in a narrower range in asymptomatic adult volunteers, especially in white populations. Distal lumbar lordosis may be a more reliable radiographic parameter to restore the lumbar lordosis distribution in preoperative planning.